Avaliação da qualidade de vida em crianças com distúrbios obstrutivos do sono pré e pós adenoidectomia ou adenotonsilectomia - Silva, Viviane Carvalho da (2005)
Objective: To evaluate the impact of sleep-disordered breathing (SDB) in the quality of life of children under treatment by the “Sistema Único de Saúde – SUS”, and the outcomes of the treatment with adenoidectomy or adenotonsillectomy in these children’s quality of life. Methods: A non-controlled intervening study was made, of the kind ‘before and after’, with an assessment component (evaluation of the quality of life). A consecutive sample of children with indication of adenoidectomy or adenotonsillectomy was recruited from the Walter Cantídio University Hospital otolaryngology clinic of the Federal University of Ceará Medical College, and the guardians answered a validated survey, specific for the evaluation of quality of life in children with SDB, the OSA-18, before the surgery and with, at least, 30 days after surgery, besides, a nasofibroscopic exam and an otolaryngology exam were done as well as the answering to a semi-structured survey about the child’s social and clinic profile, on both appointments. Results: The population under study was of 48 children with mean of 5,93 years of age (SD=2,43). The guardians’ mean of years of study was 8,29 years (SD=3,14). The most frequent symptoms were agitated sleep, apnea and snoring. The SDB complaining time average was 4,62 years (SD=2,49). The total score mean of the initial OSA-18 was 82,83 (great impact in quality of life) and after surgery was 34,15. The differences in the total scores and in the domains between the initial OSA-18 and post-surgery were all significant (p<0,00). Conclusions: Children with SDB present a relevant impact in their quality of life, and they show a dramatic improvement after surgical treatment.